KOMPETENTSIYAVIY YONDASHUV ASOSIDA BO‘LAJAK BOSHLANG‘ICH SINF O‘QITUVCHILARINING KREATIVLIK QOBILIYATLARINI RIVOJLANTIRISH - Diyora Rustam qizi, Xamidova (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2021)
This article is mainly based on a competenc approach scientific topics such as the development of creative abilities of future primary school teachers, personality orientation, creative abilities of the educator.